N021 Medication adherence and medication beliefs among women with inflammatory bowel disease in reproductive age. (16th January 2018) - Tsavdaroglou, T; Karantzas, P; Tsavdaroglou, A; Horne, R; Brokalaki, H; Mantzaris, G J
Abstract: Background: Inflammatory bowel disease (IBD) affects women from puberty to adulthood. Medication adherence and medication beliefs are a field of interest as women will probably decide to become pregnant and they must maintain disease remission throughout pregnancy. Methods: Women of reproductive age who consented to participate were asked to complete a questionnaire during their visit in the IBD outpatient clinic of the participating center. Data collection included patient demographics, education, employment, marital status, and medication characteristics. Medication adherence was assessed using 'Adherence to Refills and Medications Scale' (ARMS) and perceptions about medication using 'The beliefs about medicines questionnaire' (BMQ) which consists of specific necessity, specific concern, general harm and general over-use scale. Results: Eighty-two women [mean age (range) 32.5 (20–47) years, 54.9% with Crohn's disease, 45.1% with ulcerative colitis] were included. Medication adherence was very good and associated negatively with total number of tablets and usage of 5-ASA ( p < 0.05). Patients who summed up higher score in specific concern scale were married ( p = 0.035). These patients believed that their disease was a serious health problem (3.20 vs. 2.38, p < 0.05) and a chronic condition (3.32 vs. 2.62, p < 0.05). Furthermore, higher mean in specific concern scale was correlated with a worry of medication consumption (3.32 vs. 2.62, p < 0.05). Use of biological agents and medication adverse events indicated higher score in the necessity scale (3.77 vs. 3.40, 4.02 vs. 3.55, p < 0.05). Higher scores levels in specific necessity scale were also associated with increased number of hospital visits, with the perception that disease is a chronic condition (3.70 vs. 3.23) and a serious problem (3.84 vs. 3.27) ( p < 0.05) as well. The perception of disease severity influenced statistically the score in necessity scale with patients who appreciated their condition as severe summing up 4.40 score (vs. mild = 3.40 and moderate = 3.60, p < 0.05). Higher general harm scores referred by older ( r = 0.322, p = 0.003) patients and those who expressed worry about medication usage (2.64 vs. 2.28, p < 0.05) Conclusions: Generally, medication adherence was very good among women in reproductive age. Medication adherence was lower among women who used 5-ASA agents and was not affected from medication beliefs. This study indicates that there is a need for better communication between patient and health care providers to ameliorate patients' worries about medication usage.